William Shakespeare’s Legacy in Vocal Pedagogy: Revolutionizing the Art of Singing Through Breathing Techniques - SIMILAR, Anca (Studia Universitatis Babes-Bolyai Musica, 2024)
The article highlights the significant contributions of William Shakespeare (the vocal coach) to the art of singing in England. His approach reformed vocal pedagogy by focusing on natural breathing techniques, particularly intercostal and diaphragmatic breathing, which helped singers reduce tension and enhance lung capacity. Shakespeare's methods aimed to integrate vocal technique with the unique phonetic characteristics of the English language, ensuring clear diction and strong projection, especially in larger performance spaces like concert halls. His teachings emphasized the importance of breath control and tonal quality, which allowed singers to maintain vocal stamina during demanding performances. Shakespeare’s influence on vocal technique has left a lasting legacy, continuing to shape modern vocal pedagogy. His emphasis on natural breathing set a new standard for singers, blending technical mastery with expressive communication in vocal performance.